Reflexionamos sobre la influencia y el reconocimiento social en la adolescencia - Cardenas Sanchez, Joel Jhon Emmanuel (2020)
The present work of professional sufficiency considers the area of Personal Development, Citizenship and Civics, as an area of integral formation based on values and rights that contributes to the formation of positive attitudes of coexistence and harmony, so that the students can make decisions based on reasoning and morality when carrying out actions that affect their lives, friends, and community. This work is destined to the demonstration of strategies of the learning session called: We reflect on the influence and social recognition in adolescence. It also exposes the foundation of the area of Personal Development, Citizenship and Civics, the theoretical support considering the definition of the topic - Adolescence. Social recognition and influence of the environment. Likewise, it shows the description of the Theoretical and pedagogical support referred to the psycho-pedagogical principles, pedagogical processes, average techniques, and materials in the methodological process, as well as evaluation and the procedures and instruments of evaluation.